2019
DOI: 10.3389/fpsyg.2019.01172
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehension of Counterfactual Conditionals: Evidence From Eye-Tracking in the Visual World Paradigm

Abstract: Three experiments tracked participants’ eye-movements to examine the time course of comprehension of the dual meaning of counterfactuals, such as “if there had been oranges then there would have been pears.” Participants listened to conditionals while looking at images in the visual world paradigm, including an image of oranges and pears that corresponds to the counterfactual’s conjecture, and one of no oranges and no pears that corresponds to its presumed facts, to establish at what point in time they conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 75 publications
3
14
0
Order By: Relevance
“…Kulakova and Nieuwland (2016a) review the literature on the processing of counterfactuals and conclude that while a dual linguistic representation of both p & q and ¬p & ¬q seems to be almost part of the definition of counterfactuals, convincing evidence for the synchronous availability of both representations is hard to come by. This conclusion indirectly supports our assumption that the findings by Orenes et al (2019) RT speak against a mandatory process. However, as we will see in the section Alternatives for All?…”
Section: The Nature Of the Activation Process (Mandatory Or Strategic)supporting
confidence: 86%
See 3 more Smart Citations
“…Kulakova and Nieuwland (2016a) review the literature on the processing of counterfactuals and conclude that while a dual linguistic representation of both p & q and ¬p & ¬q seems to be almost part of the definition of counterfactuals, convincing evidence for the synchronous availability of both representations is hard to come by. This conclusion indirectly supports our assumption that the findings by Orenes et al (2019) RT speak against a mandatory process. However, as we will see in the section Alternatives for All?…”
Section: The Nature Of the Activation Process (Mandatory Or Strategic)supporting
confidence: 86%
“…Evidence from individual variation (see section Alternatives for All? Individual Differences) is also informative about the mandatory vs. strategic nature of the activation process for negation alternatives: In an eyetracking study on counterfactuals using pictorial displays reported in Orenes et al (2019) RT , participants listened to sentences like If there had been oranges, there would have been pears, having to infer that, in fact, there are no oranges and no pears. Initially, that is within about half a second, a significant group of participants increased their looks to both the real-world alternative and to the counterfactual alternative, suggesting parallel activation.…”
Section: The Nature Of the Activation Process (Mandatory Or Strategic)mentioning
confidence: 99%
See 2 more Smart Citations
“…Eye‐tracking studies also indicate they have detected both possibilities (e.g., Ferguson & Sanford, 2008; Ferguson, Sanford, & Leuthold, 2008; see also Nieuwland & Martin, 2012). For example, they look at an image corresponding to the presupposed facts more often when they hear the counterfactual than a factual conditional, and they look at an image corresponding to the conjecture equally often for both sorts of conditionals (e.g., Orenes, Garcia‐Madruga, Gomez‐Veiga, Espino, & Byrne, 2019). Accordingly, brain imaging fMRI studies show that counterfactuals activate areas related to conflict detection such as the medial prefrontal cortex (e.g., Kulakova, Aichhorn, Schurz, Kronbichler, & Perner, 2013; Van Hoeck et al, 2013).…”
Section: Conditional Suppression and Counterfactual Elevationmentioning
confidence: 99%